Potensi dan Stabilitas Hasil, serta Adaptabilitas Galur-galur Padi Gogo Tipe Baru Hasil Kultur Antera - ., Purbokurniawan; Purwoko, Bambang Sapta; Wirnas, Desta; Dewi, Iswari Saraswati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTThe objectives of the research were to obtain information on yield potential, adaptability and stability of the upland rice lines. Ten lines and two cultivars were planted at five different locations in November 2010-March 2011. In each location, the experimental design was randomized complete block design with four replications. Observation was done on grains weight per hectar. The results showed that FM1R-1-3-1 achieved the highest productivity (5.65 ton ha-1). Genotype FG1R-36-1-1 was classified as stable genotype by four yield stability analysis as followed: Francis-Kannenberg, Finlay-Wilkinson, Eberhart-Russell and AMMI. Genotypes FG1-70-2-1, FG1R-30-1-5, FG1R-30-1-4 and FG1R-30-1-3 were classified as stable genotypes by three yield stability analysis: Finlay-Wilkinson, Eberhart-Russell and AMMI. AMMI analysis showed that FG1-6-1-2, FG1-65-1-2, FG1R-30-1-1, FM1R-1-3-1, Fat-4-1-1, Situ Bagendit and Towuti as specific genotypes in certain environment.Keywords: dynamic, new plant type, specific, static, yield